Device-dependent association between paravalvar aortic regurgitation and outcome after TAVI. Issue 24 (22nd July 2014) - Dworakowski, Rafal; Wendler, Olaf; Halliday, Brian; Ludman, Peter; DeBelder, Mark; Ray, Simon; Moat, Neil; Kovac, Jan; Spyt, Tomasz; Trivedi, Uday; Hildick-Smith, David; Blackman, Dan; et al.
Abstract : Objective: The aim of the current study was to identify predictors of paraprosthetic aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) and examine its influence on short/medium-term mortality using the UK TAVI Registry. TAVI is an effective treatment for high-risk patients with severe symptomatic aortic stenosis (AS), but paraprosthetic AR has been associated with increased in-hospital and mid-term mortality. Methods: Between January 2007 and December 2011, 2584 TAVI procedures were performed in the UK. Patients undergoing 'valve-in-valve' procedures, patients with aortic regurgitation as the primary pathology and with no recorded severity of AR were excluded from this analysis (n=144). In total, therefore, 2440 patients were included. Balloon-expandable and self-expanding devices were implanted in 52.7 and 47.2%, respectively, using either transfemoral (67.7%) or non-transfemoral, surgical access (32.3%). Results: Postprocedural AR was observed in 68%, mild AR in 57% and moderate-severe in 10%. A large aortic annulus, high preprocedural transaortic gradient, and use of self-expanding valve were independent predictors of moderate-severe AR. Moderate-severe (but not mild) AR was associated with increased mortality, and this relationship appeared significant for the balloon-expandable but not the self-expanding device. Conclusions: Our data suggest that a large aortic annulus, high preprocedural transaortic gradient, and use of the self-expanding valve predict moderate-severe AR after TAVI. Such a degree of AR is associated with a significantly worse outcome with the balloon-expandable, but not with the self-expanding valve. Further studies are needed to verify this and explore potential mechanisms.